Osteoporosis knowledge and awareness among rheumatoid arthritis patients: A cross-sectional controlled study - Öykü Tomay Aksoy,; Öznur Kutluk,; İlhan Sezer, (Archives of Rheumatology, 2024)
Objectives: The aim of this study was to investigate the levels of knowledge and awareness of osteoporosis (OP) in patients with rheumatoid arthritis (RA). Patients and methods: The cross-sectional study included 100 RA patients (26 males, 74 females; mean age: 51±11 years; range, 28 to 67 years) who had not been diagnosed with OP and a control group of 50 healthy subjects (16 males, 34 females; mean age: 53±11 years; range, 29 to 70 years) between February 2022 and June 2022. The demographic data of age, sex, and education level of all the participants were recorded. Disease duration and the drugs used were recorded for the RA patients. The revised Osteoporosis Knowledge Test and the Osteoporosis Health Belief Scale questionnaires were completed by the participants. Results: There was no significant difference determined between the RA patients and the control group in OP knowledge levels. A positive correlation was determined between education level and OP knowledge level and between disease duration and OP awareness level. RA patients with a family history of OP, those in the postmenopausal period, and those using biological disease-modifying drugs thought they were at risk of OP at a higher rate. Conclusion: While the levels of knowledge and awareness of OP were determined to be similar in the RA patients and the control group, the vast majority of RA patients did not know that they were at risk of developing OP. In addition, when the data obtained in this study are taken into consideration, there appears to be a need for health strategies such as educational programs and informing RA patients about OP.